Early Global Interconnectivity across the Indian Ocean World, Volume II
XVII, 346 p. 23 illus., 3 illus. in color.
Keywords: This volume investigates the emergence and spread of maritime commerce and interconnectivity across the Indian Ocean World—the world’s first “global economy”—from a longue durée perspective. Spanning from antiquity to the nineteenth century, these essays move beyond the usual focus on geographical sub-regions or thematic aspects to foreground inter- and trans-regional connections. Focusing on the role of religion in the expansion of commerce and exchange across the region, as well as on technology and knowledge transfer, volume II covers shipbuilding and navigation technologies, porcelain production, medicinal knowledge, and mules as a commodity and means of transportation.